Sneaky blends : supercharge your health with 100 recipes using the power of purees - Lapine, Missy Chase (North Star Way, 2016)
Supercharge your health by adding vegetable and fruit purees to your soups, pastas, and baked goods! Lapine shows you how to make fifteen basic purees, and then gives you recipes for leader, cleaner, tastier meals. She includes gluten-free, vegetarian, and low-carb recipes.